Pengaruh Sikap Kepribadian Dan Gaya Kepemimpinan Terhadap Kinerja Karyawan Pada PT. Busana Prima Global (BPG) Di Bogor - Jawa Barat - Asep Sofwan Munandar; Irpat Wahyu Setyo (BULLET : Jurnal Multidisiplin Ilmu, 2022)
This study aims to determine the influence of variable Attitudes Personality, and Style of Leadership on Employee Performance in PT. PRIMA GLOBAL FLOORS. Based on the results of the research can be used as a basis for the development of economics in general and management in particular, and can be used as material comparison and input in improving employee performance in PT. PRIMA GLOBAL FLOORS. Hypothesis testing in research using multiple linear regression test, determination test (R2), t test and F test. The population in this research is population of 130 employees divided on Cadroom Division, Sample, Cutting and Marchandiser at PT. PRIMA GLOBAL FLOORS. Of the population of about 130 employees in can 57 respondents By using the Slovin formula in Umar (2007: 78). From the result of Personality Attitude Analysis (X1) through t test is bigger than t table (3,506> 2,004) and significance value 0,001 <0,05 then H0 is rejected and H1 accepted. From Personality Analysis results (X2) partially Test Findings t arithmetic greater than t table (3,294> 2,004) and significance value 0,002 <0,05 then H0 is rejected and H1 accepted. From the results of employee performance analysis (Y) simultaneous multiple test results obtained results (r) of 0.790 positive. Coefficient of Determination Adjusted R² yield of 0.625. The result of multiple linear regression test is constant (a) equal to 14,844 and F test count equal to 44,965 with significance value 0,000 <0,05. From all the test results can be seen the positive influence between Attitude Personality (X1) and Leadership Style (X2) on employee performance (Y). This proved the higher Attitude Personality and Leadership Leadership Style of employees so that will improve employee performance at PT.BUSANA PRIMA GLOBAL.